A lab-on-a-chip device for investigating the fusion process of olfactory ensheathing cell spheroids. Issue 15 (8th July 2016) - Munaz, Ahmed; Vadivelu, Raja K.; John, James A. St; Nguyen, Nam-Trung
Abstract : We report a lab-on-a-chip device for trapping and fusion of three-dimensional spheroids that assist transplantation therapy. Abstract : Understanding the process of fusion of olfactory ensheathing cell spheroids will lead to improvement of cell transplantation therapies to repair spinal cord injuries. The successful fusion of transplanted spheroids will enable alternative transplantation strategies to be developed for in vivo applications. This paper describes the use of a microfluidic device to trap and fuse olfactory ensheathing cell spheroids. The velocity, the pressure distribution in the device were simulated numerically to predict the trapping location. The simulation predicted the optimum flow rates for trapping the spheroids in the later experiments. Simulated particle trajectories were verified experimentally with tracing of fluorescent micro particles. The fusion process of the spheroids was investigated over a period of 48 hours. The microfluidic platform presented here can be used for testing potential drugs that can promote the fusion process and improve the transplantation therapy.